Conduct to be followed in case of ingestion of foreing bodies: our experience - Laviña Risso, Raúl; Maglione, Hugo; Domínguez, Carlos; Badano, José L; Valenzuela, Alvaro; Albo, Manuel (Cirugía del Uruguay, 1980)
The case material, consisting of 18 patients who had ingested alíen bodies, is from the Penitentiary Hospital of Montevideo. Of these patients, only two· had to be laparotomized since the alilé'n bo,;iy had becom<¡i stuck; in the remainder of cases it was spontaneously expelled within a period which ranged between one and 26 days. The authors favour an expectant medica! treatment, assoeiated with clinical and ra,;iiologic control.